2018
DOI: 10.1002/1873-3468.13078
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐γ enhances the wound healing effect of late EPCs (LEPCs) via BST2‐mediated adhesion to endothelial cells

Abstract: Circulating late endothelial progenitor cells (LEPCs) home to injured vessels, initiating blood vessel regeneration. This process requires the initial adhesion of LEPCs to endothelial cells within the wounded site. In this study, treating LEPCs with IFN-γ enhanced wound healing through BST2-mediated adhesion to endothelial cells. We found that IFN-γ significantly upregulated BST2 expression in both LEPCs and ECs and increased tube formation in LEPCs. Upregulated BST2 increased LEPC adhesion to ECs through a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Regarding the role of IFN-γ in skin wounds, we previously reported that IFN-γ plays a key role in the early phase of the wound healing process in a study on mice deficient in invariant natural killer T ( i NKT) cells, which are major IFN-γ-producing cells [21]. In addition, IFN-γ-treated LEPCs, which initiate blood vessel regeneration [22], or TNF-α- and IFN-γ-treated monocytes/macrophages [18] have been reported to be involved in the promotion of wound healing. In the current study, IFN-γKO mice exhibited significant attenuation in wound closure on Day 10 in association with prolonged neutrophil accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the role of IFN-γ in skin wounds, we previously reported that IFN-γ plays a key role in the early phase of the wound healing process in a study on mice deficient in invariant natural killer T ( i NKT) cells, which are major IFN-γ-producing cells [21]. In addition, IFN-γ-treated LEPCs, which initiate blood vessel regeneration [22], or TNF-α- and IFN-γ-treated monocytes/macrophages [18] have been reported to be involved in the promotion of wound healing. In the current study, IFN-γKO mice exhibited significant attenuation in wound closure on Day 10 in association with prolonged neutrophil accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Its effects on cells are remarkable and have been found to regulate the expression of thousands human genes. Although IFN‐γhas functions of anti viral, it is more notable for stimulating and regulating the immune cells 92,93 …”
Section: Proliferative Phasementioning
confidence: 99%
“…IFN‐γ is basically secreted by CD4 + and NK cells, and it contributes mainly to the activation of immune cells and has relationships with both neutrophil recruitment and cell clearance 95,96 . As for its role in wound healing, some studies show that it can enhance the healing procedure and effects, such as IFN‐γ enhances the blood vascular regeneration and wound healing through significantly upregulated BST2 expression in both LEPCs and ECs and increased tube formation in LEPCs 92 …”
Section: Proliferative Phasementioning
confidence: 99%